Entrepreneurship Ecosystem in the Colombian Caribbean Region - Cardona-Arbeláez, Diego; Tapias-Pacheco, Gioryanis (EFIM Ediciones, 2021)
Largely it has spoken of the importance of development of entrepreneurship for economic and social dynamics of a country or a particular region; It is very important to understand why the need to create ventures that generate significant changes in the reality of the society in which you run and look for strategies to their support. A review of the literature on the development of entrepreneurial ecosystems in different territories is carried out in order to present a reflection on the needs that exist in the city of Cartagena for the adequate articulation and development of high impact ventures. As a reflection, it is concluded that Cartagena has the necessary pillars to form an ecosystem that encourages high-impact entrepreneurship, but it is necessary to work from the institutions in the eradication of poverty and foster an entrepreneurial culture.